Musculoskeletal Assessment Among Quay Crane Operator at Transshipments Port - Abdullah, Nurul Diana; A Razak, Aliff Hisyam; Salwa Mahmood (Progress in Engineering Application and Technology, 2024)
Musculoskeletal disorders (MSD) involve pain affecting various body parts like joints, muscles, nerves, etc. Vehicle mechanics often face MSD risks due to ergonomic challenges at work. This study in Johor’s Port aims to link physical characteristics with factors causing musculoskeletal pain in quay crane operators. Surveys were distributed among 52 operators, analyzing factors contributing to their musculoskeletal pain. The research involved ergonomic risk assessment and various questionnaire sections covering demographics, work conditions, lifestyle, medical history, and musculoskeletal discomfort. SPSS v29 analysis showed reliable results (Cronbach’s Alpha > 0.7). The study discovered that certain body parts—upper arm, lower arm, wrist, and lower leg—are frequently affected, posing MSD risks to quay crane operators. The Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) analysis conducted at the port is a comprehensive assessment to determine the prevalence of musculoskeletal disorders among quay crane operators.